2020
DOI: 10.1111/mve.12473
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of spectrophotometry for the assessment of blood meal volume inartificially fed Culicoides imicola in South Africa

Abstract: . The volume of the blood meal of haematophagous insects will determine the number of infective particles taken up during feeding and may as such denote the minimum dose needed to infect a competent vector. Culicoides midges resort among the smallest of haematophagous vectors and determining and comparing their blood meal volumes may be challenging. Collected Culicoides imicola females were fed on defibrinated bovine blood through a Parafilm® membrane using a Hemotek® system. After feeding, the weight of pools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Estimating that C. sonorensis midges ingest a volume of 100–150 nL [ 20 , 21 ], feeding events on blood meals with titers lower than 5 log 10 PFU/mL may result in fewer than one virion being ingested, lowering the chance that midges will become infected. A previous study with intrathoracic injections of C. sonorensis midges with 200 nL volumes of bluetongue virus at 3 log 10 PFU/mL resulted in only 35% of midges becoming infected [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimating that C. sonorensis midges ingest a volume of 100–150 nL [ 20 , 21 ], feeding events on blood meals with titers lower than 5 log 10 PFU/mL may result in fewer than one virion being ingested, lowering the chance that midges will become infected. A previous study with intrathoracic injections of C. sonorensis midges with 200 nL volumes of bluetongue virus at 3 log 10 PFU/mL resulted in only 35% of midges becoming infected [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vesicular lesions and saliva contain high, measurable virus titers, and contaminate skin surfaces where midges pool-feed [ 19 ]. For VSV acquisition, midges must feed on infected hosts that are shedding virus at titers high enough to be taken up in their 100–150 nL volume blood meal (BM) [ 20 , 21 ]. Ingested virus must survive the digestive environment of the midgut, infect the midgut epithelium, and result in progeny virus crossing the basal lamina layer to disseminate into the hemolymph and subsequently infect and replicate in surrounding tissues, including the salivary glands.…”
Section: Introductionmentioning
confidence: 99%
“…Females from many Culicoides species blood-feed in swarms on a wide variety of vertebrate hosts but feed preferentially on domestic and wild ruminants and horses [34,35]. While taking small blood meals [36,37], the success of midges as vectors is primarily due to large population sizes that can be sustained with suitable climatic conditions [1]. Under standard laboratory conditions (25 • C and 70% RH), adult C. sonorensis females can complete three to four gonotrophic cycles (GC) within their three-to six-week lifetime [38].…”
Section: Introductionmentioning
confidence: 99%
“…The horse density was positively correlated with the AHS occurrence (Riddin, Venter, Labuschagne, & Villet, 2019); other studies (Bakhoum et al, 2016;Fall et al, 2015;Garros et al, 2011) also showed the very complex relationship between the AHS vectors and livestock. Female Culicoides depend mostly on blood meals as a food source (de Beer, Boikanyo, Venter, & Mans, 2020;Slama, Haouas, Mezhoud, Babba, & Chaker, 2015). In dense urban and built-up areas, where the urban population and livestock sector is continually expanding, the transmission probability of AHS may be greatly increased.…”
Section: Discussionmentioning
confidence: 99%